Towards a Domain-Specific Language to Design Adaptive Software: the DMLAS Approach - Bocanegra García, José Joaquín (2016)
An adaptive software has the ability to modify its own behavior at runtime due to changes in the users and their context, in the system, in the requirements, in the environment in which the system is deployed, and thus, give to the users a better experience. However, the development of this kind of systems is not a simple task. There are two main issues. First, there is a lack of languages to specify, unambiguously, the elements related to the design phase. As a consequence, these systems are often developed in an ad-hoc manner, without the required formalism, difficulting the process of derivation of design models to the next phases of the development cycle. Second, design decisions and the adaptation model tend to be directly implemented into the source code and not thoroughly specified at the design level. Since the adaptation models become tangled with the code, system evolution becomes more difficult. To address the above issues, this paper proposes DMLAS, a Domain-Specific Language (DSL) to design adaptive systems. As proof of concept, this paper also provides a functional prototype based on the Sirius plugin for Eclipse